2006
DOI: 10.1111/j.1472-8206.2006.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic profile of a new modified release formulation of zolpidem designed to improve sleep maintenance

Abstract: The aim of this study was to compare the relative bioavailability and the pharmacokinetic profile of a single oral dose of a zolpidem modified-release (MR) 12.5-mg formulation with those of the standard 10-mg zolpidem immediate-release (IR) formulation. Absolute bioavailabilities of oral formulations were evaluated using intravenously (i.v.) administered zolpidem as a reference. Twenty-four healthy, Caucasian, male volunteers (18-45 years old) received single doses of three oral formulations (zolpidem-MR 12.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 12 publications
(12 reference statements)
1
14
1
Order By: Relevance
“…Thus morning testing occurred 9.5 h after zolpidem-ER dosing and 5.5 h after zaleplon dosing which is approximately 1.5 h after drug should have been eliminated based on pharmacokinetic data. 23,24 Both time intervals are consistent with prior studies of SDMC involving overnight sleep. 5,6 Polysomnography (PSG) was conducted at each of the 3 overnight visits with bedtime at the subject's reported typical bedtime and time in bed held constant at 8 hours.…”
Section: Experimental Design and Proceduressupporting
confidence: 77%
See 1 more Smart Citation
“…Thus morning testing occurred 9.5 h after zolpidem-ER dosing and 5.5 h after zaleplon dosing which is approximately 1.5 h after drug should have been eliminated based on pharmacokinetic data. 23,24 Both time intervals are consistent with prior studies of SDMC involving overnight sleep. 5,6 Polysomnography (PSG) was conducted at each of the 3 overnight visits with bedtime at the subject's reported typical bedtime and time in bed held constant at 8 hours.…”
Section: Experimental Design and Proceduressupporting
confidence: 77%
“…The two hypnotics have similar mechanisms of action, both binding preferentially to the α-1 benzodiazepine receptor subunit, 22 although their durations of action differ. Zolpidem-ER has an estimated duration of action of 6-8 h, with a t 1/2 of 2.8 h and a t max of 1.5 h. 23 In contrast, zaleplon has an estimated duration of action of 3-4 h due to rapid absorption and elimination, with t 1/2 and t max both approximately one h. 24 These doses were chosen because, at the time of study, they were the recommended therapeutic doses for treatment of insomnia. In addition, residual morning sedation has not been detected with either drug at these doses when administered at bedtime, 25,26 or with zaleplon 10 mg when administered as little as 4 h before wake time (middle-of-the-night dosing).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined the pharmacokinetics of the Caucasian population after the oral administration of 10 mg zolpidem. Weinling et al reported that the C max of zolpidem in blood was 167 ± 34 ng/mL and the T max was 0.8-2.0 h. Similarly, Drover et al showed that the C max of zolpidem in blood was 167 ± 81 ng/mL and the T max 0.9-2.1 h [27,28]. These data suggest that the pharmacokinetics are different in the Caucasian and Chinese Han populations; our studies found a lower C max and a shorter T max compared with the reported pharmacokinetics in the Table 4 Pharmacokinetic parameters of zolpidem after a single oral dose of 10 mg drug.…”
Section: Pharmacokinetic Analysismentioning
confidence: 91%
“…The exposure time of the hair bulb region to ZP in blood should have an essential effect on its incorporation. Although the time changes in ZP level in the blood of the subjects was not monitored, Weinling et al (2006) reported that a single oral dose in 24 healthy men attained peak plasma ZP concentrations at approximately 1.6 hours after intake, declining with an average elimination half-life of 2.8 hours. In this study, ZP in the 0-to 1-mm segment, including the bulb, was found to be more abundant at 24 hours than at 10 hours after intake.…”
Section: Downloaded Frommentioning
confidence: 99%